CEU Graduation Ceremony 2003 (edited) - Part 1
The 12th annual CEU Graduation Ceremony was held on Wednesday, June 18, 2003 in the Vigadó Hall in the center of Budapest. During the ceremony, the university awarded 397 Master's degrees and 19 doctoral degrees. The ceremony starts with the academic procession and it opens with the words of The Master of Ceremonies Academic Pro-Rector Stefan Messmann. The introductory remarks are delivered by CEU President and Rector Yehuda Elkana. Tamás Korhecz from Legal Studies is the Alumni Speaker whilst Angela Fitzpatrick from the Department of Political Science is the Student Speaker who represents all the graduates of the academic year 2002/2003. The musical interlude is provided by Nora Bacsovics on violin. Contains images with students receiving their Master’s degrees.